Rural Communities Perceptions and Attitudes towards Environment Tourism Development - May-Chiun, Lo; T., Ramayah; Helen Lee, Hui Hui (Canadian Center of Science and Education, 2014)
Past literature has posited that tourism is one of the fastest growing sectors and has been signified as an attractive investment proposition. Rural tourism sector has been actively promoted by the Malaysian government and currently, it is considered as one of the cornerstone of Malaysia’s economic diversification strategy. On the other hand, it is important to note that stakeholder like local communities do play a crucial role in sustaining tourism development. Hence, the purpose of this study is to assess the impact of rural tourism development on the environment from the local communities’ perspectives. The environmental constructs which consists of surrounding of therural tourism destination, environment management practice, conservation of culture heritage, local satisfaction and influence of resources have been examined against local communities’ attitude towards rural tourism development. 199 respondents comprising of residents of rural tourism in Sarawak, Malaysia took part voluntarily in this study. To assess the developed model, SmarPLS 2.0 (M3) was applied based on path modelling and then bootstrapping with 200 re-samples was applied to generate the standard error of the estimate and t-values. Interestingly, the findings suggested that local communities were most concerned with the conservation of culture heritage and influence of resources when it comes to rural tourism development. Implications of these findings showed that it is crucial to understand the various concerns of the local communities for ensuring better sustainability performance especially in rural tourism setting.